Mu rhythm suppression is associated with the classification of emotion in faces. - Moore, Matthew; Franz, Elizabeth (Cognitive, Affective & Behavioral Neuroscience, 2017)
The mirror neuron system (MNS) has been mooted as a crucial component underlying human social cognition. Initial evidence based on functional magnetic resonance imaging (fMRI) suggests that the MNS plays a role in emotion classification, but further confirmation and convergent evidence is needed. This study employed electroencephalography (EEG) to examine modulations in the mu rhythm associated with the inference of emotions from facial expressions. It was hypothesised that mu suppression would be associated with classifying the emotion portrayed by facial expressions. Nineteen participants viewed pictures of facial expressions or emotion words and were asked to either match the stimulus to an emotion word or to passively observe. Mu activity following stimulus presentation was localised using a 3-D distributed inverse solution, and compared between conditions. Subtractive logic was used to isolate the specific processes of interest. Comparisons of source localisation images between conditions revealed that there was mu suppression associated with recognising emotion from faces, thereby supporting our hypothesis. Further analyses confirmed that those effects were not due to activity associated with the motor response or the observation of facial expressions, offering further support for the hypotheses. This study provides important convergent evidence for the involvement of the MNS in the inference of emotion from facial expressions.